2003
DOI: 10.1074/jbc.m207293200
|View full text |Cite
|
Sign up to set email alerts
|

Increased Protein Stability as a Mechanism That Enhances Nrf2-mediated Transcriptional Activation of the Antioxidant Response Element

Abstract: Nrf2 (NF-E2Similarly, the protein phosphatase inhibitor okadaic acid also caused an accumulation of Nrf2, whereas the reverse effects were observed with PD 98059 and U 0126, two compounds that block the activation of the MAPK/ ERK signaling cascade. These data suggest that Nrf2 is degraded by the ubiquitin-dependent pathway and that phosphorylation of Nrf2 leads to an increase in its stability and subsequent transactivation activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
393
2
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 572 publications
(445 citation statements)
references
References 43 publications
38
393
2
4
Order By: Relevance
“…Moreover, Nrf2 is reported to be a key factor in promoting gene transcription of antioxidant enzymes in HepG2 cells [82]. In the present study, compared with low or high levels of protein, at the optimal level of dietary protein, the mRNA level of Nrf2 was upregulated in the gills of grass carp.…”
Section: Optimal Level Of Dietary Protein Attenuated Inflammatory Ressupporting
confidence: 43%
“…Moreover, Nrf2 is reported to be a key factor in promoting gene transcription of antioxidant enzymes in HepG2 cells [82]. In the present study, compared with low or high levels of protein, at the optimal level of dietary protein, the mRNA level of Nrf2 was upregulated in the gills of grass carp.…”
Section: Optimal Level Of Dietary Protein Attenuated Inflammatory Ressupporting
confidence: 43%
“…On the other hand, stimulating protein expression of Nrf2 appears to be another possible mechanism. Some natural anti-oxidant agents have been shown to increase protein expression level of Nrf2 (Kwak et al, 2002;Nguyen et al, 2003;Stewart et al, 2003). In the present study, we have shown that treatment with EDG enhanced the level of Nrf2 in nucleus (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…Finally, to demonstrate that activation of endogenous Nrf2 also increases IL-8 production, cells were treated with the proteasome inhibitor MG-132, which activates the Nrf2/antioxidant pathway by preventing Nrf2 degradation [17][18][19]. IL-8 production was significantly increased in mesangial cells treated with MG-132, and this was completely blocked by prior infection of the cells with Ad.DN-Nrf2 (Fig.…”
Section: Resultsmentioning
confidence: 99%